Development of Culinary MSME Businesses Through the Implementation of E-Business and Halal Certification Assistance for MSME Products - Adif, Riandy Mardhika; Yoshanti, Ghita; Kurnia, Rahmat; HSB, Reza Firmansyah; Fahmi, Khairul (Jurnal Pengabdian UNDIKMA, 2025)
This community service aims to increase the skills and knowledge of culinary MSME players, develop an e-business system through online sales platforms, and have certified halal culinary MSME products. This service used the Participatory Action Research (PAR) method to enhance the operational skills of culinary MSMEs in Tabek Patah Village. Through training, MSME actors gained skills in halal certification, digital marketing, and online business tools such as Shopee, Tokopedia, Instagram, WhatsApp Business, and Google Maps. They learned to create digital catalogs, register their businesses on Google Maps, and obtain Business Identification Numbers (NIBs), while understanding the benefits of halal certification for market expansion. Despite challenges like limited internet infrastructure and initial skepticism, the program significantly improved MSMEs’ visibility, competitiveness, and confidence in using technology. However, continuous assistance remains crucial to sustain these advancements and address remaining barriers, ensuring long-term success in integrating technology and halal standards into their operations.